2020
DOI: 10.1089/chi.2019.0286
|View full text |Cite
|
Sign up to set email alerts
|

What Change in Body Mass Index Is Required to Improve Cardiovascular Outcomes in Childhood and Adolescent Obesity through Lifestyle Interventions: A Meta-Regression

Abstract: Background: Using meta-regression, this article aims at establishing the minimum change in BMI-standard deviation score (SDS) needed to improve lipid profiles and blood pressure in children and adolescents with obesity, to aid future trials and guidelines. Methods: Studies with participants involved in lifestyle interventions, aged 4-19 years, with a diagnosis of obesity according to defined BMI thresholds, were considered for inclusion in a large systematic review. Interventions had to report pre-and postinte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 124 publications
0
18
0
Order By: Relevance
“…Ho et al [ 54 ] showed that lifestyle interventions reduced BMI by an average of 1.25 kg/m 2 (BMI z-score: −0.1), and a significant reduction in LDL-C and TG levels and blood pressure in children and adolescents with overweight or obesity aged ≤18 years. Similarly, an analysis of data from 71 studies assessing the effect of weight reduction on the parameters of the lipid profile and blood pressure showed that a decrease in BMI z-score by > 1.2 is a likely factor in reducing the level of LDL-C and by > 0.7 for TG and by > 1 for SBP [ 60 ]. Other researchers indicate a reduction in cardiometabolic risk with a decrease in BMI z-score by ≥ 0.25 in adolescents with obesity, and greater health benefits can be achieved with a decrease in BMI z-score by a minimum of 0.5 [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ho et al [ 54 ] showed that lifestyle interventions reduced BMI by an average of 1.25 kg/m 2 (BMI z-score: −0.1), and a significant reduction in LDL-C and TG levels and blood pressure in children and adolescents with overweight or obesity aged ≤18 years. Similarly, an analysis of data from 71 studies assessing the effect of weight reduction on the parameters of the lipid profile and blood pressure showed that a decrease in BMI z-score by > 1.2 is a likely factor in reducing the level of LDL-C and by > 0.7 for TG and by > 1 for SBP [ 60 ]. Other researchers indicate a reduction in cardiometabolic risk with a decrease in BMI z-score by ≥ 0.25 in adolescents with obesity, and greater health benefits can be achieved with a decrease in BMI z-score by a minimum of 0.5 [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…A reduction of only 0.86%-3.59% of BMI could lead to beneficial effect on HBP in our study. However, a recent meta-analysis of 54 lifestyle intervention studies in pediatric populations showed that reduction of >1 mean BMI SDS is related to improved SBP [7]. Considering the difference of race, and age in different studies, it is hard to compare or make a final quantification of the minimum favorable BMI reduction for metabolic health.…”
Section: Association Between Risk Of Hbp and Different Quintiles Of Bmi Or Whtr Change In The Obese Childrenmentioning
confidence: 99%
“…The association between obesity and blood pressure (BP) levels or hypertension has been demonstrated in numerous cross-sectional studies [4][5][6]. Also, intervention studies against obesity showed that weight management will additionally benefit BP profile [7]. But in a natural life course, it remains unclear whether the change of general or abdominal fat accumulation status without intervention would impact the risk of HBP in childhood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published meta-regression study [19] concluded that a minimum 0.6 decrease in BMI-SDS is imperative in order to attain any improvement in fat mass. Furthermore, a systematic review with meta-analysis [20] and several meta-regression studies [21,22] concluded that reductions in BMI-SDS are likely to improve cardiovascular outcome in childhood and adolescent obesity; nevertheless, at present, they are unable to recommend a de nite value of BMI-SDS reduction indispensable to improve markers of metabolic health. In other words, the reduction in BMI-SDS required to improve both body composition and the pro le of cardiovascular risk factors by means of lifestyle interventions has not yet been fully established.…”
Section: Introductionmentioning
confidence: 99%